Relation of Plasma Coagulation Factor VII and Fibrinogen to Carotid Artery Intima-Media Thickness - Sosef, M N; Bosch, J G; van Oostayen, J; Visser, T; Reiber, J H C; Rosendaal, F R (Thrombosis and Haemostasis, 1994)
Plasma clotting factor VII and plasma fibrinogen have been claimed as independent risk factors for occlusive cardiovascular disease. The aim of this study was to investigate whether these coagulation parameters affect early atherosclerosis, additional to their possible effect on arterial thrombosis.We used high-resolution quantitative ultrasonography to measure carotid intima-media thickness in 121 healthy volunteers, aged 18 to 56 years. It has previously been demonstrated that an increased artery wall thickness is seen in advanced atherosclerosis. To validate our methodology for relatively young individuals, we assessed the association of intima-media thickness with the risk-factor status of our subjects, by including classical cardiovascular risk factors, e. g. age, sex, serum cholesterol, smoking habits and blood pressure. Thereafter, we studied the effect of factor VII and fibrinogen plasma levels on carotid intimamedia thickness, as well as that of polymorphisms of the factor VII and fibrinogen genes.All classical risk factors except smoking and family history were associated with intima-media thickness. When adjusted for by multivariate linear regression analysis, age, blood pressure and cholesterol appeared to be independent determinants of intima-media thickness. Factor VII and fibrinogen levels showed no association in multivariate analysis with intima-media thickness. We conclude that artery wall thickness measurement by ultrasound is a useful tool to investigate the role of clotting factors in early atherosclerosis. Factor VII and fibrinogen levels in young and middle-aged volunteers have no association with early artherosclerotic vessel wall changes.